Organic bananas: up, up and away - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
international workshop on Production and Marketing of Organic Bananas by Smallholder Farmers held in Santo Domingo, Dominican Republic, from 31 November to 3 December 1999